Hebrew poetry in the Bible a guide for understanding and for translating - Zogbo, Lynell 1948-; Wendland, Ernst R. 1944- (Miami, FL United Bible Societies, 2020)
"In this book the authors try to convince exegetes and translators that rendering biblical poetry as poetry in languages around the world is a worthy and realistic goal, and they provide strategies and means to understand the biblical text and to recreate poetic renderings in these host languages"--
Includes bibliographical references and index
Keywords: Hebrew poetry, Biblical -- History and criticism; Hebrew poetry, Biblical -- Translating